Proteolytic Profiles of Aspergillus caespitosus, A. jensenii and A. neotritici, and a Novel Peptidase with Plasmin-like Activity for Biomedicine and Pharmacology - Klyagin, Sergey; Maklakova, Irina; Tomic, Nina; Shestakova, Anna; Pieckova, Elena; Osmolovskiy, Alexander (Current Pharmaceutical Biotechnology, 2025)
<span class=
Keywords: proteases